Preparation method of coal-based coating pitch for co-production of two different lithium negative electrode materials

CN117264648BActive Publication Date: 2026-10-27鞍钢化学科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311306696.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2026-10-27
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

本发明不仅解决了煤沥青高效高附加值利用问题,同时进一步优化产品结构,延伸产业链、降低生产成本

Benefits of technology

[0024]1)本发明利用煤沥青作为原料,加工程度高、产品附加值高,能够优化产品结构,延伸产业链、降低生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117264648B_ABST
    Figure CN117264648B_ABST
Patent Text Reader

Abstract

The present application relates to a preparation method of coal-based coating pitch for two different lithium battery negative electrode materials, 1) the raw material pitch is mixed with the extractant uniformly and then placed in a settling tank, after static settling separation, light phase oil and heavy phase oil are obtained; 2) the light phase oil obtained in step 1) is sent into a distillation kettle, after distillation recovery of the extractant, purified coal pitch is obtained; 3) the purified coal pitch obtained in step 2) is sent into an oxidation crosslinking reaction kettle, under the protection of nitrogen or inert gas, the crosslinking agent and catalyst are added and mixed and stirred uniformly, oxidation crosslinking reaction is carried out, and coating pitch A is obtained; 4) the coating pitch A obtained in step 3) is sent into a thin film evaporator, and coating pitch B is obtained by evaporation. The method can obtain two different coal-based coating pitches for lithium battery negative electrode materials at the same time, which are used for liquid phase coating and solid phase coating respectively, expand the application range, the product flexibility is higher, adapt to market changes, reduce the enterprise risk.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery anode material production, and particularly relates to a method for preparing coal-based coated pitch for co-producing two different lithium battery anode materials. Background Technology

[0002] Graphite, as a negative electrode material for lithium-ion batteries, possesses advantages such as high specific capacity, good cycle performance, low lithium intercalation / deintercalation platform, and low cost, making it the most commercially valuable lithium-ion battery negative electrode material. However, due to the poor compatibility of graphite with organic solvent electrolytes, excessive SEI film forms on the surface of the negative electrode material. This not only consumes a large amount of lithium and causes significant irreversible capacity loss, but also increases interfacial impedance, causing electrochemical kinetic barriers, leading to graphite layer dissociation and even exfoliation, resulting in capacity decay and decreased cycle performance. To improve the electrochemical performance of graphite materials, research has begun on modifying and altering graphite materials. Modification methods include doping with other elements, surface oxidation treatment, and surface coating modification.

[0003] Coating modification is one of the effective methods to improve the electrochemical performance of graphite anode materials. Commonly used coating methods include chemical vapor deposition (CVD), solid-phase coating, and liquid-phase coating. Among these, coating is widely used due to its low cost and simple process; most commercially available graphite anode materials currently employ this method. Generally, in the coating modification of graphite materials, resin-based materials with hard carbon structures or pitch-based materials with soft carbon structures are typically used. The coating material decomposes under high-temperature conditions to form an amorphous carbon layer adhering to the graphite surface, reducing the active end faces on the graphite surface and thus improving the compatibility between graphite and the electrolyte. Pitch has advantages such as low price, high carbon residue, and good fluidity at high temperatures, and is widely used as a coating material. Under high temperature and inert conditions, asphalt can crack on the surface and inside of graphite particles to form an amorphous carbon layer. This layer not only coats the surface of the graphite material but also penetrates into the interior of the graphite particles through the micropores within the graphite. This improves the tap density and electronic conductivity of the graphite material, thereby enhancing the initial charge-discharge efficiency and cycle performance of the graphite anode material.

[0004] This invention provides a method for preparing coal-based coated pitch for co-producing two different lithium-ion battery anode materials, which can be used for liquid-phase coating and solid-phase coating, expanding the application range and increasing product flexibility. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing coal-based coated pitch for the co-production of two different lithium-ion battery anode materials. The method uses widely available and inexpensive coal tar pitch as raw material, resulting in coated pitch with good ductility. This coated pitch can alter the appearance and structure of the anode material, improve the compatibility between the anode material and the electrolyte, reduce the specific surface area, and increase the reversible specific capacity and initial coulombic efficiency of the anode material. Furthermore, this invention can simultaneously obtain coal-based coated pitch for two different lithium-ion battery anode materials, which can be used for liquid-phase coating and solid-phase coating respectively, expanding the application range, increasing product flexibility, adapting to market changes, and reducing enterprise risk. This invention not only solves the problem of efficient and high-value-added utilization of coal tar pitch but also further optimizes the product structure, extends the industrial chain, and reduces production costs.

[0006] To achieve the above objectives, the present invention employs the following technical solution:

[0007] A method for preparing coal-based coated pitch for co-producing two different lithium-ion battery anode materials includes the following steps:

[0008] 1) After the raw material asphalt and extractant are mixed evenly, they are placed in a settling tank. After static settling and separation, light phase oil and heavy phase oil are obtained.

[0009] The raw material asphalt is one or a mixture of several of the following: coal-based soft asphalt, coal-based medium-temperature asphalt, coal-based modified asphalt, and low-temperature dry distillation coal tar pitch.

[0010] The extractant is one or a mixture of several of the following: kerosene, wash oil, anthracene oil, dianthracene oil, phenol oil, naphthalene oil, benzene, toluene, and xylene.

[0011] The mixing ratio of raw bitumen to extractant is 1:0.5–2 by mass; the length-to-diameter ratio of the settling tank is 1–20:1, the settling temperature is 80–200℃, and the settling time is 0.5–12 h; the ratio of light phase oil to heavy phase oil after separation is 5–9.5:5–0.5 by mass; the density of the light phase oil is 0.85–1.1 g / cm³. 3 The density of the heavy phase oil is 1.0–1.35 g / cm³. 3 .

[0012] 2) The light phase oil obtained in step 1) is fed into a distillation kettle, and after distillation to recover the extractant, purified coal tar pitch is obtained.

[0013] For atmospheric distillation, the distillation conditions are a vapor phase temperature of 280–350℃ and a final residence time of 0.5–2h; for vacuum distillation, the distillation conditions are a vapor phase temperature of 200–300℃, a vacuum degree of 0.01–0.09MPa, and a final residence time of 0.5–2h.

[0014] The softening point of the purified coal tar pitch is 20–45°C, and the content of quinoline insoluble matter is 0–0.2%.

[0015] 3) The purified coal tar obtained in step 2) is fed into an oxidative crosslinking reactor. Under the protection of nitrogen or inert gas, crosslinking agent and catalyst are added, mixed and stirred evenly, and oxidative crosslinking reaction is carried out to obtain coated asphalt A.

[0016] The inert gas is high-purity nitrogen or high-purity argon. The crosslinking agent is one or a mixture of several of the following: terephthalic acid, anisole, benzophenone, formaldehyde, trioxymethylene, paraformaldehyde, benzaldehyde, terephthalaldehyde, p-methylbenzaldehyde, cinnamaldehyde, salicylaldehyde, terephthaloyl dichloro, divinylbenzene, acetaldehyde, furfural, and their polymers or isomers and derivatives.

[0017] The catalyst is one or a mixture of several of the following: sulfonic acid, methanesulfonic acid, ethylsulfonic acid, benzenesulfonic acid, aminosulfonic acid, p-methylbenzenesulfonic acid, p-hydroxybenzenesulfonic acid, p-aminobenzenesulfonic acid, p-acetaminobenzenesulfonic acid, and their isomers or homologues.

[0018] According to the mass ratio, the ratio of raw material asphalt: crosslinking agent: catalyst is 1:0.01~0.2:0.01~0.2; the oxidative crosslinking reaction conditions are: heating rate of 0.5~5℃ / min, oxidation temperature of 120~350℃, and oxidation time of 1~20h.

[0019] The coated asphalt A is mainly used for liquid phase coating. Its softening point is 110-150℃, the content of toluene insoluble matter is 8-15%, the content of quinoline insoluble matter is 0-3%, the coking value is 35-55%, the ash content is 0-0.5%, and the moisture content is 0-1%.

[0020] 4) The coated asphalt A obtained in step 3) is fed into a thin-film evaporator and evaporated to obtain coated asphalt B.

[0021] The evaporation conditions for the thin-film evaporator are: evaporation temperature of 300-450℃, pressure of less than 1000Pa, and effective residence time of 0.01-10min.

[0022] The coated bitumen B is mainly used for solid phase coating. Its softening point is 210-260℃, the content of toluene insoluble matter is 20-45%, the content of quinoline insoluble matter is 3-8%, the coking value is 65-80%, the ash content is 0-0.5%, and the moisture content is 0-1%.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] 1) This invention uses coal tar pitch as raw material, which has a high degree of processing and high product added value, and can optimize product structure, extend industrial chain and reduce production costs.

[0025] 2) The method of the present invention can simultaneously obtain two different lithium battery anode materials coated with coal-based pitch, which can be used for liquid phase coating and solid phase coating respectively, thus expanding the application scope, increasing product flexibility, adapting to market changes, and reducing enterprise risk.

[0026] 3) The preparation method of this invention is simple, the product has excellent performance, the coated asphalt has good ductility, it can change the appearance and structure of the negative electrode material, improve the compatibility between the negative electrode material and the electrolyte, reduce the specific surface area, and improve the reversible specific capacity and first coulombic efficiency of the negative electrode material. Attached Figure Description

[0027] Figure 1 This is a 3000x scanning electron microscope image of the asphalt-coated negative electrode material of Example 1 after carbonization at 1000℃.

[0028] Figure 2 This is a 3000x scanning electron microscope image of the asphalt-coated negative electrode material of Example 2 after carbonization at 1000℃.

[0029] Figure 3 This is a 4000x scanning electron microscope image of the asphalt-coated negative electrode material of Example 3 after carbonization at 1000℃.

[0030] Figure 4 This is a 5000x scanning electron microscope image of the asphalt-coated negative electrode material of Example 4 after carbonization at 1000℃. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the specific implementation methods of this invention will be further described below in conjunction with the embodiments. The following embodiments are used to specifically illustrate the content of this invention. These embodiments are only general descriptions of the content of this invention and do not limit the content of this invention.

[0032] Example 1:

[0033] The raw material asphalt was coal-based soft asphalt with a softening point of 30℃ and a quinoline insoluble content of 1.83%. Kerosene and wash oil were mixed uniformly at a mass ratio of 0.8:1 to prepare a mixed extractant. Then, a mixture of coal-based soft asphalt and extractant at a mass ratio of 1:0.7 was prepared and placed in a settling tank with a length-to-diameter ratio of 8:1 for sedimentation separation. The settling temperature was 130℃, and the settling time was 3 hours. The light phase oil and heavy phase oil were then separated at a mass ratio of 8:2. The density of the light phase oil was determined to be 1.0 g / cm³. 3 The density of the heavy phase oil is 1.3 g / cm³. 3The light phase oil was fed into a distillation kettle, and the vapor phase was heated to 330℃ for 1.5 hours. The extractant was then recovered by atmospheric distillation to obtain purified coal tar pitch with a softening point of 25℃ and a quinoline-insoluble content of 0.01%. The purified coal tar pitch was then fed into an oxidative crosslinking reactor. Under high-purity nitrogen protection, a crosslinking agent and catalyst were added at a mass ratio of purified coal tar pitch: paraformaldehyde: benzenesulfonic acid = 1:0.05:0.03. The mixture was stirred until homogeneous, and the temperature was increased to 130℃ at a rate of 1℃ / min. The mixture was then stirred at this constant temperature for 5 hours to carry out the oxidative crosslinking reaction, yielding coated pitch A for liquid phase coating. This coated pitch had a softening point of 115℃, a toluene-insoluble content of 8.56%, a quinoline-insoluble content of 0.94%, a coking value of 36.88%, an ash content of 0.05%, and a moisture content of 0.5%. The obtained coated bitumen A was fed into a thin-film evaporator. Evaporation was carried out at 330℃, pressure below 300Pa, and effective residence time of 4 minutes to obtain coated bitumen B for solid-phase coating. This coated bitumen B had a softening point of 235℃, a toluene-insoluble content of 28.69%, a quinoline-insoluble content of 5.22%, a coking value of 70.29%, an ash content of 0.22%, and a moisture content of 0.56%. Graphite material was coated with coated bitumen A and coated bitumen B. After carbonization at 1000℃ and graphitization at 2800℃, the specific surface area increased from 5.204 m² / s². 2 / g decreased to 3.163m 2 / g and 2.875m 2 / g, the 0.1C reversible capacity increased from 343.2mAh / g to 348.66mAh / g and 352.45mAh / g, and the first coulombic efficiency increased from 92.45% to 95.32% and 96.35%.

[0034] Example 2:

[0035] The raw material asphalt was coal-based medium-temperature asphalt with a softening point of 95℃ and a quinoline insoluble content of 6.82%. The asphalt was mixed thoroughly at a mass ratio of 1:1.5 with wash oil, and then placed in a settling tank with a length-to-diameter ratio of 9:1 for sedimentation separation. The settling temperature was 140℃, and the settling time was 3 hours. The light phase oil and heavy phase oil were then separated at a mass ratio of 7:3. The density of the light phase oil was determined to be 0.9 g / cm³. 3 The density of the heavy phase oil is 1.2 g / cm³. 3The light phase oil was fed into a distillation kettle, held at a final gas phase temperature of 260℃ for 1 hour, and then subjected to vacuum distillation at a vacuum degree of 0.08 MPa to recover the extractant, yielding purified coal tar pitch with a softening point of 30℃ and a quinoline-insoluble content of 0.05%. The purified coal tar pitch was then fed into an oxidative crosslinking reactor. Under the protection of high-purity argon, a crosslinking agent and catalyst were added at a mass ratio of purified coal tar pitch: terephthalaldehyde: methanesulfonic acid = 1:0.1:0.05, mixed thoroughly, and heated to 170℃ at a rate of 2℃ / min, and stirred for 4 hours to carry out the oxidative crosslinking reaction, yielding coated pitch A for liquid phase coating. This coated pitch had a softening point of 128℃, a toluene-insoluble content of 10.20%, a quinoline-insoluble content of 1.22%, a coking value of 40.56%, an ash content of 0.12%, and a moisture content of 0.14%. The obtained coated bitumen A was fed into a thin-film evaporator. Evaporation was carried out at 350℃, pressure below 500Pa, and effective residence time of 2 minutes to obtain coated bitumen B for solid-phase coating. This coated bitumen B had a softening point of 255℃, a toluene-insoluble content of 42.12%, a quinoline-insoluble content of 7.34%, a coking value of 78.46%, an ash content of 0.36%, and a moisture content of 0.28%. Graphite material was coated with coated bitumen A and coated bitumen B. After carbonization at 1000℃ and graphitization at 2800℃, the specific surface area increased from 5.204 m² / s². 2 / g decreased to 2.545m 2 / g and 2.603m 2 / g, the 0.1C reversible capacity increased from 343.2mAh / g to 358.78mAh / g and 356.73mAh / g, and the first coulombic efficiency increased from 92.45% to 98.02% and 96.89%.

[0036] Example 3:

[0037] The raw material asphalt was coal-modified asphalt with a softening point of 120℃ and a quinoline insoluble content of 8.52%. It was mixed thoroughly with coal-modified asphalt at a mass ratio of 1:1 to toluene and then placed in a settling tank with a length-to-diameter ratio of 10:1 for sedimentation separation. The settling temperature was 140℃ and the settling time was 3 hours. The light phase oil and heavy phase oil were then separated at a mass ratio of 8:2. The density of the light phase oil was determined to be 1.06 g / cm³. 3 The density of the heavy phase oil is 1.34 g / cm³. 3The light phase oil was fed into a distillation kettle, the vapor phase was heated to 300℃, and held for 1 hour. The extractant was then recovered by atmospheric distillation to obtain purified coal tar pitch with a softening point of 42℃ and a quinoline-insoluble content of 0.12%. The purified coal tar pitch was then fed into an oxidative crosslinking reactor. Under high-purity nitrogen protection, a crosslinking agent and catalyst were added at a mass ratio of purified coal tar pitch: cinnamaldehyde: ethyl sulfonic acid = 1:0.12:0.08. The mixture was stirred until homogeneous, and the temperature was increased to 200℃ at a rate of 3.5℃ / min. The mixture was then stirred at this constant temperature for 12 hours to carry out the oxidative crosslinking reaction, yielding coated pitch A for liquid phase coating. This coated pitch had a softening point of 142℃, a toluene-insoluble content of 13.88%, a quinoline-insoluble content of 2.11%, a coking value of 52.90%, an ash content of 0.15%, and a moisture content of 0.08%. The obtained coated bitumen A was fed into a thin-film evaporator at an evaporation temperature of 380℃, a pressure below 90Pa, and an effective residence time of 6 minutes to obtain coated bitumen B for solid-phase coating. B had a softening point of 246℃, a toluene-insoluble content of 36.55%, a quinoline-insoluble content of 6.75%, a coking value of 73.66%, an ash content of 0.33%, and a moisture content of 0.35%. Graphite material was coated with coated bitumen A and coated bitumen B, and after carbonization at 1000℃ and graphitization at 2800℃, the specific surface area increased from 5.204 m² / s². 2 / g decreased to 2.265m 2 / g and 1.867m 2 / g, the 0.1C reversible capacity increased from 343.2mAh / g to 357.96mAh / g and 360.88mAh / g, and the first coulombic efficiency increased from 92.45% to 97.86% and 98.23%.

[0038] Example 4:

[0039] The raw material asphalt was low-temperature dry distilled coal tar pitch with a softening point of 85℃ and a quinoline-insoluble content of 0.58%. Kerosene and naphthalene oil were mixed uniformly at a mass ratio of 0.8:1 to prepare a mixed extractant. The mixture was then further mixed at a mass ratio of low-temperature dry distilled coal tar pitch to extractant of 1:1.2 and placed in a settling tank with a length-to-diameter ratio of 12:1 for sedimentation separation. The settling temperature was 150℃, and the settling time was 2 hours. The light phase oil and heavy phase oil were then separated at a mass ratio of 6:4. The density of the light phase oil was determined to be 0.85 g / cm³. 3 The density of the heavy phase oil is 1.18 g / cm³. 3The light phase oil was fed into a distillation kettle, held at a final gas phase temperature of 260℃ for 1 hour, and then subjected to vacuum distillation at a vacuum degree of 0.09 MPa to recover the coking light oil, yielding purified coal tar pitch with a softening point of 34℃ and a quinoline-insoluble content of 0.02%. The purified coal tar pitch was then fed into an oxidative crosslinking reactor. Under the protection of high-purity argon, a crosslinking agent and catalyst were added at a mass ratio of purified coal tar pitch: anisole: benzenesulfonic acid = 1:0.08:0.03, mixed thoroughly, and heated to 135℃ at a rate of 1.5℃ / min, and stirred for 5 hours to carry out the oxidative crosslinking reaction, yielding coated pitch A for liquid phase coating. This coated pitch had a softening point of 132℃, a toluene-insoluble content of 12.12%, a quinoline-insoluble content of 1.45%, a coking value of 42.55%, an ash content of 0.14%, and a moisture content of 0.12%. The obtained coated bitumen A was fed into a thin-film evaporator at an evaporation temperature of 360℃, a pressure below 200Pa, and an effective residence time of 5 minutes to obtain coated bitumen B for solid-phase coating. B had a softening point of 228℃, a toluene-insoluble content of 23.54%, a quinoline-insoluble content of 4.65%, a coking value of 68.97%, an ash content of 0.21%, and a moisture content of 0.62%. Graphite material was coated with coated bitumen A and coated bitumen B, and after carbonization at 1000℃ and graphitization at 2800℃, the specific surface area increased from 5.204 m² / s². 2 / g decreased to 2.344m 2 / g and 2.675m 2 / g, the 0.1C reversible capacity increased from 343.2mAh / g to 358.33mAh / g and 357.89mAh / g, and the first coulombic efficiency increased from 92.45% to 97.22% and 96.87%.

Claims

1. A method for preparing coal-based coated pitch for the co-production of two different lithium-ion battery anode materials, characterized in that, The methods and steps include the following: 1) After the raw asphalt and extractant are mixed evenly, they are placed in a settling tank and separated by static settling to obtain light phase oil and heavy phase oil; 2) The light phase oil obtained in step 1) is fed into a distillation kettle, and after distillation to recover the extractant, purified coal tar pitch is obtained; The softening point of the purified coal tar pitch is 20–45℃, and the content of quinoline insolubles is 0–0.2%. 3) The purified coal tar obtained in step 2) is fed into an oxidative crosslinking reactor. Under the protection of nitrogen or inert gas, crosslinking agent and catalyst are added, mixed and stirred evenly, and oxidative crosslinking reaction is carried out to obtain coated asphalt A. The coated asphalt A is used for liquid phase coating, and has a softening point of 110-150℃, a toluene-insoluble content of 8-15%, a quinoline-insoluble content of 0-3%, a coking value of 35-55%, an ash content of 0-0.5%, and a moisture content of 0-1%. 4) The coated asphalt A obtained in step 3) is fed into a thin-film evaporator and evaporated to obtain coated asphalt B; The coated bitumen B is used for solid-phase coating, with a softening point of 210-260℃, a toluene-insoluble content of 20-45%, a quinoline-insoluble content of 3-8%, a coking value of 65-80%, an ash content of 0-0.5%, and a moisture content of 0-1%.

2. The preparation method of coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1, characterized in that, The raw material pitch mentioned in step 1) above is one or a mixture of several of the following: coal-based soft pitch, coal-based medium-temperature pitch, coal-based modified pitch, and low-temperature dry distillation coal pitch. The extractant is one or a mixture of several of the following: kerosene, wash oil, anthracene oil, dianthracene oil, phenol oil, naphthalene oil, benzene, toluene, and xylene.

3. The preparation method of coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1 or 2, characterized in that, In step 1) above, the mixing ratio of raw asphalt to extractant is 1:0.5-2 by mass; the length-to-diameter ratio of the settling tank is 1-20:1, the settling temperature is 80-200℃, and the settling time is 0.5-12h; the ratio of light phase oil to heavy phase oil after separation is 5-9.5:5-0.5 by mass; the density of the light phase oil is 0.85-1.1 g / cm³. 3 The density of the heavy phase oil is 1.0–1.35 g / cm³. 3 .

4. The preparation method of coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1, characterized in that, In step 2) above, the distillation conditions for atmospheric distillation are a vapor phase temperature of 280–350°C and a final residence time of 0.5–2 h; the distillation conditions for vacuum distillation are a vapor phase temperature of 200–300°C, a vacuum degree of 0.01–0.09 MPa, and a final residence time of 0.5–2 h.

5. The preparation method of coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1, characterized in that, In step 3) above, the crosslinking agent is one or a mixture of several of the following: terephthalic acid, anisole, benzophenone, formaldehyde, trioxymethylene, paraformaldehyde, benzaldehyde, terephthalic acid, p-methylbenzaldehyde, cinnamaldehyde, salicylaldehyde, terephthaloyl dichloro, divinylbenzene, acetaldehyde, furfural, and their polymers or isomers and their derivatives. The catalyst is one or a mixture of several of the following: sulfonic acid, methanesulfonic acid, ethylsulfonic acid, benzenesulfonic acid, aminosulfonic acid, p-methylbenzenesulfonic acid, p-hydroxybenzenesulfonic acid, p-aminobenzenesulfonic acid, p-acetaminobenzenesulfonic acid, and their isomers or homologues.

6. The method for preparing coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1 or 5, characterized in that, In step 3) above, the mass ratio of raw material asphalt: crosslinking agent: catalyst is 1:0.01~0.2:0.01~0.2; the oxidative crosslinking reaction conditions are: heating rate of 0.5~5℃ / min, oxidation temperature of 120~350℃, and oxidation time of 1~20h.

7. The preparation method of coal-based coated pitch for co-producing two different lithium-ion battery anode materials according to claim 1, characterized in that, In step 4) above, the evaporation conditions of the thin-film evaporator are: evaporation temperature of 300-450℃, pressure of less than 1000Pa, and effective residence time of 0.01-10min.

Citation Information

Patent Citations

  • High-softening-point coal-tar pitch production method

    CN102732280A

  • Novel high-performance asphalt special for carbon material and preparation method thereof

    CN111826187A